Eldearly Preparedness In Faces Of Tornado Disaster In The District Sitinjo - Risdiana Melinda Naibaho (JURNAL KEPERAWATAN DAN FISIOTERAPI (JKF), 2023)
A Tornado is a strong wind or it can also be called a big, very strong storm with a whirlwind at a certain speed. Disasters cannot be predicted at any time and can occur. The need for disaster preparedness to prevent the risk of human casualties, material losses, environmental damage and psychological impacts that threaten and disrupt people's lives and livelihoods. Elderly is a group that is very at risk before, during and after a disaster occurs, because the elderly have many chronic diseases, functional decline, cognitive impairment, dementia, and physical limitations. Preparedness is an action taken in anticipation of a disaster to ensure that the actions taken can be. This research is a quantitative study using the research design "cross sectional". This research was conducted to determine the preparedness and factors related to the preparedness of the elderly in facing the tornado disaster in Sitinjo Village, Sitinjo District, Dairi Regency in 2021. The population in this study were 70 elderly people in the work area of Sitinjo District, the sampling technique was stratified random sampling and met the inclusion criteria. The results of the study obtained the majority of respondents in the elderly, low education, female gender, lack of knowledge, have a positive attitude toward disaster preparedness of the Tornado wind, have experienced the Tornado disaster, are not prepared for the Tornado wind disaster. The results of chi square statistical test showed that there is no relationship between age, gender and the preparedness of the elderly in the face of Tornado disaster. There is a relationship between education p-value 0.022, knowledge p-value 0.01, attitude p-value 0.002, and experience p-value 0.021 with the preparedness for the cyclone disaster. It is hoped that the elderly can increase the knowledge and preparedness for the putting wind disaster by participating in socialization, training and conducting disaster simulations and it is necessary to coordinate with the relevant Dairi Regency BPBD to conduct socialization and mitigation of Tornado wind disaster preparedness